The mechanism and microstructure of silicanizing process on mild steel substrate in the medium of silica sand - Fmy, Y. (Asian Research Publishing Network, 2016)
This paper presents the work carried out to determine the morphology and mechanical properties of coating deposited layer that formed onto mild steel substrate using a new silicanizing method. The result shows that the coating silicanized layer consisting of FeSi, Fe2SiO4, FeSiO3 and SiO2 phase was successfully formed on the mild steel after subjecting to heat treatment process of 1000 Â°C for 4 hours. This layer of â500Î¼m thickness and also established that higher temperature and elongated deposition/adhesion time resulted an increase in SiO2 concentration on the substrate (mild steel). Â©2006-2016 Asian Research Publishing Network (ARPN).